Synthesis of Eu3+ ‑Doped ZnO/Zn2SiO4 Composite Phosphor for Potent Optoelectronic Applications - Suhail Huzaifa Jaafar; Mohd Hafiz Mohd Zaid; Khamirul Amin Matori; Yazid Yaakob; Haslinawati Binti Mohd Mustapha (Springer Nature, 2024)
Indexed by WOS/SCOPUS/ERA